Edukasi Pengelolaan Wakaf Uang di Rumah Sakit Zainab Pekanbaru - Putra, P. Adiyes; Nurnasrina, Nurnasrina; Pulungan, Lanni Afriani (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2025)
Effective and transparent management of cash waqf is a crucial component in supporting the sustainability and development of social institutions, including Islamic hospitals. Zainab Hospital Pekanbaru, as a sharia-based healthcare institution, requires a comprehensive understanding of the mechanisms, regulations, and potential optimization of cash waqf to improve service quality and provide better healthcare facilities for the community, particularly the underprivileged (dhuafa). This community service activity aims to enhance the knowledge and awareness of the staff, management, and nazhir (waqf managers) at Zainab Hospital regarding the management of cash waqf in accordance with sharia principles and applicable regulations. The methods used in this program include counseling, interactive discussions, and case simulations. The results show an improvement in participants’ understanding of the concept of cash waqf, the role of nazhir, and the legal-formal procedures involved in its management. This educational initiative is expected to serve as a foundation for Zainab Hospital to implement a professional and sustainable cash waqf program, considering the significant potential of waqf as a source of financing for healthcare services.